2020
DOI: 10.1111/codi.15387
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical subspecialization on patient outcomes following emergency colorectal resections in the north of England: a retrospective cohort study

Abstract: Aim Emergency colorectal surgery is associated with significant morbidity and mortality. Most general surgeons have a subspecialty, which forms the focus of their elective work, allowing development of specialist skill sets. The aim of this study was to assess the impact of consultant subspecialization on patient outcomes following emergency colorectal resections. Methods Data were requested for all emergency admissions under a general surgeon between 1 January 2002 and 31 December 2016 within the north of Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The body of evidence supporting specialist fellowship training programs is considerable; demonstrating a signi cant impact on surgical pro ciencies and patient care outcomes [27][28][29][30][31][32][33]. Other research also points towards a consistent increase in the number of applicants pursuing surgical sub-specialities [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The body of evidence supporting specialist fellowship training programs is considerable; demonstrating a signi cant impact on surgical pro ciencies and patient care outcomes [27][28][29][30][31][32][33]. Other research also points towards a consistent increase in the number of applicants pursuing surgical sub-specialities [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent large studies report an increase in mortality in patients operated on by surgeons whose area of expertise was not in the area of the pathology, and for colorectal patients not operated on by specialist colorectal surgeons there were lower rates of laparoscopy and an increase in return to the operating room [ 30 ], although these results must be interpreted with caution as factors such as the urgency of the procedure may not have been fully accounted for. Another study shows lower mortality and stoma formation if an emergency colorectal resection is done by a colorectal subspecialist [ 31 ]. Solutions may include partnering across specialties in the management of complex emergency surgical patients [ 32 , 33 ].…”
Section: Experience Of Surgeon and Anesthesiologistmentioning
confidence: 99%
“…Finally, surgical sub‐specialisation and the emergence of the ‘emergency surgeon’ raises questions about who should care for patients presenting acutely with colorectal cancer. A recent publication in this journal [6] reported that 30‐day mortality after emergency colorectal resection (not all for cancer) was significantly lower (11.8% vs. 15.2%) if the responsible consultant was a colorectal surgeon rather than another general surgeon.…”
mentioning
confidence: 99%